PENGERTIAN ADMINISTRASI PENDIDIKAN, PERKEMBANGAN ADMINISTRASI PENDIDIKAN DI INDONESIA: Studi Kepustakaan Tentang Konsep dan Dinamika Administrasi Pendidikan di Indonesia - Takdirmin; Musdalifah Sadar; Nurfadilah; Razin Muqsit (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Educational administration plays a strategic role in supporting the success of educational implementation. Good educational management not only supports the smooth running of the learning process but also contributes to the achievement of national educational goals. This study aims to examine the definition of educational administration and its development in Indonesia. The research method used is a qualitative approach with a literature study method, involving the review of various written sources such as books, scientific journals, and relevant laws and regulations.The results of the study show that educational administration is the process of managing educational activities which includes planning, organizing, implementing, and supervising all educational resources in a systematic and sustainable manner. The development of educational administration in Indonesia has undergone a shift from a centralized system to a more decentralized one, particularly through the implementation of school-based management. This change aims to improve the effectiveness, efficiency, and quality of educational management. Nevertheless, the implementation of educational administration still faces various challenges, especially regarding human resource competence and the managerial capacity of educational institutions. Therefore, continuous strengthening of educational administration is required to support the realization of a quality and competitive national education system